Interfacial interaction mechanism of graphene/phenolic resin composites: A molecular dynamics study. Issue 1 (January 2021) - Bian, C; Yan, N; Zhu, G W; Qu, H J; Guan, Y W; Li, H Y; Luan, T; Gong, J L
Abstract: The outstanding thermal and mechanical properties of graphene/phenolic resin (G/PR) composites are largely related with the interfacial interactions. The interfacial properties of the G/PR composites were studied with molecular dynamics method, based on dozens of G/PR and graphene oxide/PR (GO/PR) interface models. The results showed that, p-π/π-π and hydrogen bond interactions are the main interactions between the G/PR and GO/PR interfaces, respectively. Strong interfacial interactions were formed between the crosslinked PRs and GO layer grafted with oxygen-containing groups. The obtained results will be beneficial to guide the design and preparation of G/PR composites with special performances.